Ultrasonic phased array technology for the non-destructive testing of marble sculptures. (2nd January 2017) - Tiefensee, Frank; Weber, Peter; Kunz, Simon; Pamplona, Marisa; Simon, Stefan
Abstract : The medical ultrasonic phased array technology was modified for the non-destructive testing of marble sculptures and the feasibility of the approach was evaluated. For this purpose, 1 MHz, 64-channel phased array electronic and phased array transducers were developed. The specifications of the electronics and the transducers are presented and discussed. Ultrasound images of inner structures of a marble sculpture are presented. The problem of the acoustic matching layers for different states of deterioration is discussed and the developments in view of a suitable matching layer solution are presented. This matching layer is combined with a new coupling technique that protects the marble surface. The results of experiments on ultrasound phantoms and on a marble sculpture are presented.